A cost-benefit analysis of capital requirements for the Danish economy - Jakob Guldbæk Mikkelsen; Jesper Pedersen (Danmarks Nationalbank, 2017)
We analyse the costs and benefits of increasing capital requirements for Danish banks. Costs can be close to 0 if banks suspend dividend payments for a period of time as banks accumulate capital and if investors' required return falls. The latter implies that the Modigliani-Miller effect is close to 1 in the long run. Suspension of dividends mitigates costs in an economically significant way, no matter what is assumed about the Modigliani-Miller effect. The estimates are upper bounds primarily because the model implies an elasticity of 1 for cost of capital for both banks and firms. We show that financial crises have persistent effects on GDP. We find the present value of output losses to be around 84 percent. A reduction in the probability of a financial crisis from a 1 percentage point increase in capital ratios gives an expected benefit of 1 percent of GDP. Based on Danish data and using models for the Danish economy, we thus confirm findings in studies for other economies: The benefits outweigh the social costs of increasing capital ratios. In this sense, there is nothing special about the Danish economy. We argue that it is beneficial to raise capital requirements accompanied by a demand for suspension of dividends and to do so in expansion periods when banks' profits are relatively high. If the required return on equity does not fall in response to higher levels of capital, this outcome could imply, not that equity is more expensive than debt, but a lack of competition. This must be addressed with other instruments. – – Vi analyserer fordele og omkostninger ved at øge kapitalkrav for danske banker. Omkostningerne kan være tæt på 0, hvis bankerne ikke udbetaler dividender i to år, og hvis det krævede afkast for at investere i banker falder i takt med, at ny kapital akkumuleres i bankerne. Den sidste antagelse indebærer, at Modigliani-Miller effekten er tæt på 1 på langt sigt. Hvis bankerne ikke udbetaler dividender, er omkostningerne betydeligt lavere for givne antagelser om Modigliani-Miller effekten. Estimaterne er en øvre grænse, primært fordi den anvendte model indebærer en elasticitet på 1 for højere omkostninger for både banker og virksomheder. Vi viser, at finansielle kriser har persistente effekter på BNP. Hvis vi antager moderate permanente effekter, finder vi, at nutidsværdien af tabene ved finansielle kriser er omkring 84 pct. af BNP. Et fald i sandsynligheden for en finansiel krise ved et højere kapitalkrav på 1 procentpoint giver en forventet fordel på 1 pct. af BNP. Vi bekræfter hermed, ved brug af data for Danmark og modeller udviklet til analyse af dansk økonomi, resultater fra andre studier for andre lande: Fordelene ved at øge kapitalkrav er større end omkostningerne. Vi argumenterer for, at det kan være fordelagtigt at kræve stop for dividendeudbetalinger i takt med højere kapitalkrav, og at øge kapitalkrav i konjunkturopgange. Hvis afkastkravet ikke falder i takt med, at bankerne bliver mere sikre, kan det afspejle svag konkurrence og ikke, at bankkapital er dyrere end gæld.
Keywords: C01; C10; C58; E32; E37; E44; C18; 330; Financial Regulation; Models; Financial Markets; Financial Stability